Implementasi Prinsip Keadilan dalam Kontrak Asuransi Pasca Putusan Mahkamah Konstitusi Nomor 83/PUU-XXII/2024 atas Pasal 251 Kitab Undang-Undang Hukum Dagang (KUHD) - Safitri, Niken Febriani; Elisatris Gultom; Sudaryat (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda Palembang, 2025)
The Constitutional Court Decision Number 83/PUU-XXII/2024 concerning Article 251 of the Indonesian Commercial Code (KUHD) represents a pivotal moment in strengthening legal protection for policyholders within insurance contracts in Indonesia. Prior to this ruling, Article 251 KUHD authorized insurers to unilaterally revoke insurance policies upon discovering discrepancies in the information provided by policyholders, including unintentional errors. Such a provision created an imbalance in the legal position between insurer and insured, and often led to injustice in insurance practices. Through this decision, the Constitutional Court annulled the aforementioned provision, emphasizing the importance of applying the principles of justice and proportionality in contractual relationships. This study aims to examine the implementation of the principle of justice in insurance contracts following the Court's ruling. The analysis focuses on both juridical and practical impacts on the process of forming and executing insurance agreements. This research employs a normative juridical method, with statutory, conceptual, and case study approaches. The findings indicate that the revocation of Article 251 KUHD has shifted the burden of disclosure, placing greater emphasis on fairness in evaluating the balance of rights and obligations between the parties. The principle of justice now plays a central role, replacing the insurer's previous unilateral dominance. This condition necessitates adaptation from both the insurance industry and regulatory authorities in formulating technical policies that prioritize consumer protection and contractual equity.